Urban Sustainability and the Local Politics of Digital Twins: the Cases of Bologna and Milan - Ernesto d'Albergo; Giorgio Giovanelli (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
To address the complexity of sustainable urban development, policymakers are making increasing use of digital technology tools, now including AI and urban digital twins (UDTs). The aims of the article are to shed light on the political implications of UDTs uses in urban policy and governance aimed at sustainability and to understand from a perspective of political sociology factors influencing processes of UDTs design and implementation. Research questions regard the local politics of UDTs for sustainability analyzed through the lenses of policy frames, contexts, regulation and data governance and value. Responses are based on evidence from the comparative analysis of two case studies: Bologna and Milan, carried out through desk and field research (analysis of documents and interviews). Local agencies lead to different approaches and, potentially, outcomes, made possible by the diversity and plasticity of UDT models, systems and purposes, as well as by the elasticity and adaptability to different spatial contexts of the policy paradigm of urban sustainability. Two patterns of the local politics of UDTs emerge in Bologna and Milan, in which above all the roles of public actors and businesses are different. Logics of action, practices and forms of coordination are transferred from the broader systems of urban governance and political economy to the more circumscribed systems of action of UDTs.